Current Limitations of Murine Models in Oncology for Ascorbate Research - Campbell, Elizabeth J.; Dachs, Gabi U. (Frontiers in Oncology, 2014)
The role of vitamin C (ascorbate) in cancer prevention, tumor growth, and treatment is of intense public interest. Clinical trial data have been sparse, contradictory, and highly controversial, and robust pre-clinical data are required for progress. This paper reviews pre-clinical models and their limitations with respect to ascorbate research. Most studies have utilized animals able to synthesize ascorbate and thus are not ideal models of the human condition. More recently, genetically modified mouse models have become available; yet, all studies compared healthy and scorbutic mice. The majority of investigations to date concluded that increased ascorbate led to decreased tumor growth, but data on mechanisms and doses are inconclusive. Clinically relevant animal studies are still required to convince a generally sceptical medical audience of the potential worth of ascorbate as an adjunct to therapy.